2015
DOI: 10.1039/c4ra10498f
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt aluminate nanoparticles supported on MIL-101 structure: catalytic performance investigation

Abstract: Novel heterogeneous catalysts composed by CoAl2O4 nanoparticles supported on MIL-101(Cr) framework exhibiting remarkable catalytic performance for thioanisole oxidation under sustainable conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The comparison of NL with Cr­(III)-MOF-NPs and MIL-101-Cr-MOF/CoAl-1@MIL­(Cr) “reported by Granadeiro et al,” spectra is shown in Figure b. For Cr­(III)-MOF-NPs, the peaks among 3715 and 3100 cm –1 are assigned to NH 2 and H 2 O molecules, respectively.…”
Section: Results and Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The comparison of NL with Cr­(III)-MOF-NPs and MIL-101-Cr-MOF/CoAl-1@MIL­(Cr) “reported by Granadeiro et al,” spectra is shown in Figure b. For Cr­(III)-MOF-NPs, the peaks among 3715 and 3100 cm –1 are assigned to NH 2 and H 2 O molecules, respectively.…”
Section: Results and Discussionmentioning
confidence: 80%
“…The results were in tremendous consistency with that calculated theoretically for the proposed formula of monomeric Cr Fourier Transform Infrared. The comparison of NL with Cr(III)-MOF-NPs and MIL-101-Cr-MOF/CoAl-1@MIL(Cr) "reported by Granadeiro et al, 43 " spectra is shown in Figure 2b. For Cr(III)-MOF-NPs, the peaks among 3715 and 3100 cm −1 are assigned to NH 2 and H 2 O molecules, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…29 CoAl 2 O 4 nanoparticles embedded in MIL-101(Cr) have proved to be efficient catalysts for oxidative catalysis. 30 Recently MIL-101(Cr) and its phospho-tungstic acid (PTA) composite material have been studied as heterogeneous acid catalysts in the acetalization of aldehydes with alcohols. 31 Functionalized MIL-101(Cr) has been investigated for heterogeneous catalysis in the condensation reaction of aldehydes with alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…The crystalline peaks were consistent with those in the previously reported pure MIL-101­(Cr) data, thereby demonstrating the successful synthesis of highly crystalline MIL-101­(Cr)-Br. The XRD pattern of MIL-101­(Cr)-Br contained noticeable crystalline peaks at 2θ = 5.1, 8.4, and 9.0°, which corresponded to crystalline-plane diffraction of the (531), (882), and (911) planes. , …”
Section: Resultsmentioning
confidence: 97%